Synthesis and characterization of 1,3,4-thiadiazole compounds derived from 4-phenoxybutyric acid for antimicrobial activities - Muğlu, Halit; Şener, Nesrin; Mohammad Emsaed, Hamza Ahmet; Özkınalı, Sevil; Özkan, Osman Emre; Gür, Mahmut (Elsevier BV, 2018)
Abstract New 1,3,4-thiadiazole compounds were synthesized through the cyclization reaction of 4-phenoxybutyric acid and N-phenylthiosemicarbazide derivatives with phosphorous oxychloride. The structures of 1,3,4-thiadiazole compounds (I–XII) were clarified using spectroscopic methods such as FT-IR, 1H NMR, and 13C NMR. Moreover, their antibacterial activities were tested against gram negative bacteria (Salmonella enteritidis, Salmonella typhimurium, Enterobacter aerogenes, Salmonella infantis, Salmonella kentucky, Escherichia coli) and gram positive bacteria (Staphylococcus aureus, Bacillus subtilis, Enterococcus durans) using a disk diffusion method. An antifungal activity experiment was further carried out against Candida albicans using the disk diffusion method. While these compounds presented antibacterial activity against S. aureus, they did not show antimicrobial activity against gram negative (E. coli, E. aerogenes, S. kentucky, S. enteritidis, S. typhimurium, S. infantis) and gram positive (B. subtilis) bacteria, and the fungi C. albicans.
Keywords: ,3,4-Thiadiazole; IR and NMR Spectroscopies; Antimicrobial Activity; 13. Climate action; 3. Good health